Evaluation of two membrane‐based microextraction techniques for the determination of endocrine disruptors in aqueous samples by HPLC with diode array detection. Issue 22 (27th October 2017) - Luiz Oenning, Anderson; Lopes, Daniela; Neves Dias, Adriana; Merib, Josias; Carasek, Eduardo
Abstract: In this study, the viability of two membrane‐based microextraction techniques for the determination of endocrine disruptors by high‐performance liquid chromatography with diode array detection was evaluated: hollow fiber microporous membrane liquid–liquid extraction and hollow‐fiber‐supported dispersive liquid–liquid microextraction. The extraction efficiencies obtained for methylparaben, ethylparaben, bisphenol A, benzophenone, and 2‐ethylhexyl‐4‐methoxycinnamate from aqueous matrices obtained using both approaches were compared and showed that hollow fiber microporous membrane liquid–liquid extraction exhibited higher extraction efficiency for most of the compounds studied. Therefore, a detailed optimization of the extraction procedure was carried out with this technique. The optimization of the extraction conditions and liquid desorption were performed by univariate analysis. The optimal conditions for the method were supported liquid membrane with 1‐octanol for 10 s, sample pH 7, addition of 15% w/v of NaCl, extraction time of 30 min, and liquid desorption in 150 μL of acetonitrile/methanol (50:50 v/v) for 5 min. The linear correlation coefficients were higher than 0.9936. The limits of detection were 0.5–4.6 μg/L and the limits of quantification were 2–16 μg/L. The analyte relative recoveries were 67–116%, and the relative standard deviations were less than 15.5%.